Hubungan Ferritin Serum dengan Berat Badan dan Tinggi Badan Pada Penderita Thalasemia Β Mayor - Muhammad Abi Daud (Jurnal Ilmiah Kesehatan Sandi Husada, 2020)
Background: One marker that can be used to measure excess iron in the body is to measure ferritin plasma levels in the case of iron buildup in the pituitary gland, it interferes with the secretion of Growth Hormone (GH), Thyroid-Stimulating Hormone (TSH), and Adrenocorticotropic Hormone (ACTH) Objectives: Knowing the relationship of serum ferritin with growth disorders in thalassaemia β major patients at Abdul Moeloek Hospital in 2020. Method: Research in the form of observational observation of the latitude, conducted in February-April 2020 serum ferittin levels are obtained by reviewing the observation of medical record data. and measurement of body weight and height based on the BMI formula to see growth disorders in the β-major thalassemia patients. Results: Analysis of research data using Fisher's statistical trials. During the study obtained a total of 60 samples. There is a meaningless relationship between levels of serum ferritin with growth disorder (P = 0,002) in Thalassaemia major.